A peregrinação e seus enigmas: o desvendamento no encontro do devoto com o santo vivo rumo ao santuário de São Francisco do Canindé - Oliveira, Marcelo João Soares de (2011)
This work is an object of research investigating the pilgrimage of devotees of St. Francis of Assisi which takes place annually in the city of Canindé, pointing out the puzzles of this journey and his discovery of the unveiling by living saint and union with him. It aims to show the duality of the pilgrimage that brings devotion to the holy dead, as conceived by the Church and devotion to the living saint, as perceived by devotees. It is intended also present a new approach to the phenomenon of pilgrimage in Canindé in the current context and make the way of construction of the identity of the devotee. The study, although based on religion, breaks the social situation of abandonment that is the pilgrim, which justifies research into the causes that lead to gather in a large group whose members are linked by faith in the living saint. Sustains the hypothesis that in the pilgrimage, the devotee unveils the riddle of living saint, discovering himself through awareness of their subjectivity and their position in the world, which leads him to overcome his troubles and losses . For harvests data will be performed procedures such as observation of the field, focusing on the rituals, attitudes and way of being of the pilgrim, pilgrims and interviews with the survey of his life history, collection and analysis of the liturgical and devotional materials, such as former -wishes, prayers, chants, prayers, letters. Data analysis will be made by an assessment of thematic framing in qualitative research. To print more reliability to the research will be performed two interviews, taped or transcribed, to be compared. The results show that in the pilgrimage city of Canindé in search of the living saint Francis of Assisi is established as the stage of overcoming struggles and oppression of the devotees, giving them the opportunity to establish an affective relationship with the holy, to build their identity and reframe his life